The metabolic response in fish to mildly elevated water temperature relates to species-dependent muscular concentrations of imidazole compounds and free amino acids. (April 2017) - Geda, Fikremariam; Declercq, Annelies M.; Remø, Sofie C.; Waagbø, Rune; Lourenço, Marta; Janssens, Geert P.J.
Abstract: Fish species show distinct differences in their muscular concentrations of imidazoles and free amino acids (FAA). This study was conducted to investigate whether metabolic response to mildly elevated water temperature (MEWT) relates to species-dependent muscular concentrations of imidazoles and FAA. Thirteen carp and 17 Nile tilapia, housed one per aquarium, were randomly assigned to either acclimation (25 °C) or MEWT (30 °C) for 14 days. Main muscular concentrations were histidine (HIS; P <0.001) in carp versus N-α -acetylhistidine (NAH; P <0.001) and taurine (TAU; P =0.001) in tilapia. Although the sum of imidazole (HIS+NAH) and TAU in muscle remained constant over species and temperatures ( P >0.05), (NAH+HIS)/TAU ratio was markedly higher in carp versus tilapia, and decreased with MEWT only in carp ( P <0.05). Many of the muscular FAA concentrations were higher in carp than in tilapia ( P <0.05). Plasma acylcarnitine profile suggested a higher use of AA and fatty acids in carp metabolism ( P <0.05). On the contrary, the concentration of 3-hydroxyisovalerylcarnitine, a sink of leucine catabolism, ( P =0.009) pointed to avoidance of leucine use in tilapia metabolism. Despite a further increase of plasma longer-chain acylcarnitines in tilapia at MEWT ( P =0.009), their corresponding beta-oxidation products (3-hydroxy-longer-chain acylcarnitines) remained constant. Together with higher plasma non-esterified fatty acids (NEFA) in carp ( P =0.001), the latter shows that carp, being a fatter fish, more readily mobilises fat than tilapia at MEWT, which coincides with more intensive muscular mobilization of imidazoles. This study demonstrates that fish species differ in their metabolic response to MEWT, which is associated with species-dependent changes in muscle imidazole to taurine ratio. Highlights: This is the first comparative study that demonstrated the species-dependent metabolic response to a mild elevation of water temperature of the muscular concentrations of imidazoles and FAA in aquatic organisms. The study compared two fish species (carp versus tilapia) that clearly differed in muscular concentration profile and demonstrated that muscular concentrations of imidazoles and TAU in fish respond to water temperature in a species dependent manner. There are differences in metabolism between fish species, and even interaction between species and water temperature. The difference in metabolism between fish species and species-temperature interaction was demonstrated by changes in muscle imidazole to taurine ratio. The present results point to a species-dependent relationship between nutrient use and muscular concentrations of imidazoles and FAA as a response to water temperature. The results are also expected to give rise to a range of follow-up studies by research groups active in the domains of imidazole-related compounds and global warming.